Machining and CNC Technology - Mike Fitzpztrick (Mc Graw Hill, 2005)
Besar file 319 MB, berisi file: LA (McGraw-Hill licenses), Mastercam, Media (content, plugin, supporting), section_25_files, dan Xtras (X32 file).